An-Nadzâir Al-Mukhâdi’ah Lî At-Ta’lîm Al-Lughah Al-‘Arabiyyah Fî Mu’jam Al-Lughah Al Baliyah - Fanoni May; Fajar Sidik (Mauriduna: Journal of Islamic Studies, 2020)
النظائر المخادعة هي الكلمات في لغة ما تتشابه في نطقها أو شكلها مع كلمات أخرى لكنهما تختلفان في المعنى. تهدف هذه الدراسة إلى اكتشاف النظائر المخادعة في معجم اللغة البالية لتيسير عملية تعليم اللغة العربية، لوجود الظنّ أن بعض المفردات في لغة الأم لمتعلم اللغة العربية تشبه اللغة العربية تشبيه تاما. وإنجاز هذه الدراسة كانت على طريقة منهج علمي وهو: المنهج الوصفي التحليلي، وذلك بجمع النظائر المخادعة بين اللغة العربية واللغة البالية في معجم اللغة البالية ، وبعد انتهاء تحليلها وصف أوجه التشابه والاختلاف بين اللغتين. ولقد كشفت هذه الدراسة أن عدد النظائر المخادعة بين اللغة العربية والبالية في هذا معجم ثلاثة وثمنون كلمة، ومن تلك الكلمات أغلب هذه الكلمات متشابهة باللغة العربية نطقا ناقصا والأخرى متشابهة باللغة العربية نطقا تاما. وقد تم وصف الكلمات (من حرفL إلى S نموذجا) وتحليلها. أما طريقة استفادة تلك الكلمات في تعليم اللغة العربية للباليين فتكون من خلال دراسة النصوص والحوارات والتدريب عليها. Homonyms are words in a language that are similar in their pronunciation or shape to other word in other language but they differ in meaning. This study aims to discover the homonyms in KAMUS IDEAL BAHASA BALI dictionary to explain their uses in facilitating the process of teaching Arabic to beginners, because there is an assumption that some vocabulary in the mother tongue of a learner of Arabic is very similar to Arabic. The method used by the researcher in this study was based on a scientific descriptive analysis research method, by combining the homonyms between Arabic and Balinese languages on the KAMUS BALI dictionary and in order to analyze and describe the similarities and differences between the two languages. This study revealed that the number of homonyms between the Arabic and Balinese languages in KAMUS BALI dictionary is eighty-three words. Among the words are those which are used in daily conversation and those which are not used daily. Most of them are completely similar in Arabic with incomplete pronunciation while the others ares completely similar with Arabic. They were described and analyzed from the letter L to R. These words can be utilized and benefitted in teaching Arabic to the Balinese through reading texts, dialogues and training in which these words.